Treatment of Periodontitis Affecting Human Primary Teeth-A Systematic Review - Protyusha Guha Biswas; Anusha Mohan; Eswar Kandaswamy (MDPI AG, 2023)
The aim of this systematic review is to report the treatment options (Intervention) and outcomes (O) for primary teeth affected by periodontitis (Population) and if the treatment of primary teeth can prevent the spread of periodontitis to permanent teeth (Outcomes). The following databases were searched for papers published before December 2022: PubMed, Embase, Web of Science, and Ebscohost. Studies on children affected by periodontitis involving the primary teeth were included and those on children who presented with periodontitis as a manifestation of systemic disease were excluded. Narrative synthesis and methodological quality assessments were performed for the included studies. Three interventional studies (without a control group) that evaluated treatments involving scaling and root planing (SRP with antibiotics) and extraction were included (total n = 60 patients). Additionally, twelve case reports/case series articles (n = 19 patients) were identified. The diagnoses ranged from aggressive periodontitis to juvenile periodontitis and pre-pubertal periodontitis. Based on a limited number of published studies, it was found that the early treatment of periodontitis affecting the primary teeth using SRP and systemic antibiotics resulted in favorable improvements in PD and CAL. Limited evidence suggests that SRP and the extraction of the primary teeth involved have the potential to prevent periodontitis affecting permanent teeth. Future trials are required to standardize the treatment protocols and to confirm these findings.